2008
DOI: 10.1287/mnsc.1070.0851
|View full text |Cite
|
Sign up to set email alerts
|

Confidentiality and Information Sharing in Supply Chain Coordination

Abstract: We consider information sharing in a decentralized supply chain where one manufacturer supplies to multiple retailers competing in price. Each retailer has some private information about the uncertain demand function which he may choose to disclose to the manufacturer. The manufacturer then sets a wholesale price based on the information received. The information exchange is said to be confidential if the manufacturer keeps the received information to herself, or nonconfidential if she discloses the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
231
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(241 citation statements)
references
References 30 publications
9
231
1
Order By: Relevance
“…This stream has also investigated the impact of information sharing on the price structure within a supply chain [22,38]. The issue of confidentiality in sharing of sensitive information within a supply chain was analyzed by Li and Zhang [23]. Mishra et al [25] showed that both the manufacturer and the retailer have incentives to share distorted information.…”
Section: Related Literaturementioning
confidence: 99%
“…This stream has also investigated the impact of information sharing on the price structure within a supply chain [22,38]. The issue of confidentiality in sharing of sensitive information within a supply chain was analyzed by Li and Zhang [23]. Mishra et al [25] showed that both the manufacturer and the retailer have incentives to share distorted information.…”
Section: Related Literaturementioning
confidence: 99%
“…Similar information paradigms have been studied in the supply chain management literature (see, e.g., Li and Zhang 2008;Anand and Goyal 2009;Shin and Tunca 2010;Taylor and Xiao 2010;Ha et al 2011;Choi et al 2013;Li et al 2014). For example, Choi et al (2013) study strategic information sharing in a two-level supply chain and show that return policy can achieve win-win between supplier and retailer.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Fierce competition and advent of information technology promote the cooperation of companies in the supply chain (Ha & Tong, 2008), information sharing is viewed as one of the key elements for successful supply chain management and coordination. Information sharing can reduce the risk brought by asymmetric incomplete information ,cut down lead time ,mitigate bullwhip effect and reduce total cost and increase total supply chain profit Li & Zhang, 2008;. The global performance of a supply chain can be highly improved by information sharing between its members at different levels (MontoyaTorres & Ortiz-Vargas, 2014).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Information sharing can reduce the risk brought by asymmetric incomplete information, cut down lead time, mitigate bullwhip effect Li & Zhang, 2008;. Many research concerns the reason of bullwhip effect.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation